THEOLOGY OF JUSTICE AND GENDER MARGINALIZATION: A HERMENEUTIC ENGAGEMENT WITH FARID ESACK’S ISLAMIC THOUGHT - Sa’dan, Masthuriyah; M. Mukhtasar Syamsuddin; Agus Himmawan Utomo (UIN Raden Mas Said Surakarta, 2025)
The gender minority group of transgender individuals living with HIV/AIDS in Indonesia experiences poverty and multiple layers of vulnerability, leading to discrimination and social stigma. This discrimination is further exacerbated by governmental actions against transgender individuals living with HIV/AIDS (ODHA) on theological grounds. This study aims to analyse the rights to justice of transgender individuals living with HIV/AIDS in Indonesia through the lens of Farid Esack's theology of justice. This research employs a qualitative literature-based approach, utilising primary data sources that include Esack's works and writings on transgender individuals, comprising books, journal articles, documents, and other relevant materials. The data analysis technique applied is hermeneutics, which seeks to derive meaning and understanding (verstehen) in order to elucidate the text's inner significance. The findings of this study suggest that Farid Esack's concept of theology of justice, particularly the notion of tauhid, encompasses not only transcendental relationships but also social interactions. Moreover, those who attain the status of muttaqien are characterised by their concern for the suffering of others. This attitude of empathy and inclusion towards oppressed groups (mustad'afien) reflects an awareness of Allah's nature, which is both rahman and rahim. The contribution of this study lies in its efforts to reconstruct contextual theology to advocate for the rights of the gender minority group of HIV/AIDS-affected waria in Indonesia.